2009
DOI: 10.1038/onc.2008.485
|View full text |Cite
|
Sign up to set email alerts
|

Profiling YB-1 target genes uncovers a new mechanism for MET receptor regulation in normal and malignant human mammary cells

Abstract: Basal-like breast cancers (BLBCs) are aggressive tumors with high relapse rates and poor survival. We recently reported that >70% of primary BLBCs express the oncogenic transcription/translation factor Y-box binding protein-1 (YB-1) and silencing it with small interfering RNAs (siRNAs) attenuates the growth of BLBC cell lines. To understand the basis of these earlier findings, we profiled YB-1:DNA complexes by chromatin immunoprecipitation (ChIP)-on-chip. Several tumor growth-promoting genes such as MET, CD44,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
113
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 36 publications
8
113
0
2
Order By: Relevance
“…Within the nucleus, YB-1 binds to the inverted CCAAT elements known as YB-1-responsive elements (YREs) to affect transcription (Didier et al, 1988). Given the importance of YB-1 in breast cancer we sought to understand how it globally regulates gene expression and therefore a genome-wide promoter screen was performed using the NimbleGen chromatin immunoprecipitation (ChIP)-onchip (COC) platform (Finkbeiner et al, 2009). The COC, which provided the basis for the present study, demonstrated a 17.05-fold enrichment of PIK3CA promoter hybridization to the microarray as compared to the input control, suggesting that YB-1 may control the expression of PIK3CA by direct promoter occupancy.…”
Section: Introductionmentioning
confidence: 99%
“…Within the nucleus, YB-1 binds to the inverted CCAAT elements known as YB-1-responsive elements (YREs) to affect transcription (Didier et al, 1988). Given the importance of YB-1 in breast cancer we sought to understand how it globally regulates gene expression and therefore a genome-wide promoter screen was performed using the NimbleGen chromatin immunoprecipitation (ChIP)-onchip (COC) platform (Finkbeiner et al, 2009). The COC, which provided the basis for the present study, demonstrated a 17.05-fold enrichment of PIK3CA promoter hybridization to the microarray as compared to the input control, suggesting that YB-1 may control the expression of PIK3CA by direct promoter occupancy.…”
Section: Introductionmentioning
confidence: 99%
“…114 The same argument applies to other Y/CCAAT promoters, which YB-1 was shown to activate, including DNA Pola, 115 cyclin A, cyclin B1, 116 where many reports have also demonstrated an NF-Y dependence (Farina et al 117 ; reviewed in Gurtner et al 118 ). For other YB-1 targets, such as EGFR, PIK3CA, MET and CD44, [119][120][121][122] the Y/CCAAT, as it has been characterized genetically and bioinformatically, is absent.…”
Section: Nf-y Is the Sequence-specific Ccaat Factormentioning
confidence: 99%
“…121,126 We analyzed the data for 430 000 ChIP-Seq peaks in three cancer cell types and could not identify a Y/CCAAT sequence, either searching for known TFBS or with de novo motif discovery tools. 127 This is uncommon for a sequence-specific TF, whose logo is usually recognizable within the bound peaks, but not unheard of: 60 in many cases, one can identify either a new logo or one of those characterized for other TFs.…”
Section: Nf-y Is the Sequence-specific Ccaat Factormentioning
confidence: 99%
“…It is widely expressed across a broad range of tissues, but in vivo data on the biological function of YBX1 is limited because the Ybx1 null mouse is embryonic lethal [192,193]. YBX1 is as broad in its cellular function as in its expression, involved in transcription, translational control and splicing depending on the cell type expressing it and post-translational modifications [11,24,36,39,41,42,[48][49][50][51][193][194][195][196]. Perhaps because of its myriad cellular roles, there is little consistency about when developmentally it is expressed across tissues, or where inside the cell it is located, with it being reported in the nucleus, cytoplasm, or shuttling between the two based on posttranscriptional modifications [41,188,194,[196][197][198].…”
Section: Introductionmentioning
confidence: 99%
“…YBX1 has a broad range of reported functions including transcriptional regulation and splicing depending on the cell type expressing it and post-translational modifications [11,49,51,[193][194][195][196][197][198][199]212]. The other major function of YBX1 is in RNA translational control, generally through mRNA sequestration and prevention of transcript degradation, although some studies suggest that it can positively regulate translation as well [24, 36, 39-42, 45-48, 50, 52, 53].…”
Section: Introductionmentioning
confidence: 99%